The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/gtmb.2015.0163
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Methylation Abnormalities Among Estonian Patients Selected by Clinical Diagnostic Scoring Systems for Silver–Russell Syndrome and Beckwith–Wiedemann Syndrome

Abstract: Aims: To study the frequency of methylation abnormalities among Estonian patients selected according to published clinical diagnostic scoring systems for Silver-Russell syndrome (SRS) and Beckwith-Wiedemann syndrome (BWS). Materials and Methods: Forty-eight patients with clinical suspicion of SRS (n = 20) or BWS (n = 28) were included in the study group, to whom methylation-specific multiplex ligation-dependant probe amplification analysis of 11p15 region was made. In addition, to patients with minimal diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…They found that 22% of patients with diagnosed epimutations had methylation defects of additional imprinted loci, and among patients with clinical features of an imprinting disorder but no molecular diagnosis, methylation anomalies were diagnosed in 8%, including missed and unexpected molecular diagnoses. Vals et al [2015b] also detected the hypomethylation of PLAGL1 (6q24) and IGF2R (6q25) genes without 11p15 imprinting disorder and clinical features of 6q24-related transient neonatal diabetes mellitus in one patient with the highest BWS clinical scoring.…”
Section: Clinical Overlap Of Srs and Bws With Other Methylation Abnormentioning
confidence: 81%
See 2 more Smart Citations
“…They found that 22% of patients with diagnosed epimutations had methylation defects of additional imprinted loci, and among patients with clinical features of an imprinting disorder but no molecular diagnosis, methylation anomalies were diagnosed in 8%, including missed and unexpected molecular diagnoses. Vals et al [2015b] also detected the hypomethylation of PLAGL1 (6q24) and IGF2R (6q25) genes without 11p15 imprinting disorder and clinical features of 6q24-related transient neonatal diabetes mellitus in one patient with the highest BWS clinical scoring.…”
Section: Clinical Overlap Of Srs and Bws With Other Methylation Abnormentioning
confidence: 81%
“…Other minor features are neonatal hypoglycemia, hemihyperplasia, and characteristic facial features. A rec- [Kotzot et al, 1995;Eggermann et al, 1997;Preece et al, 1997;Netchine et al, 2007;Abu-Amero et al, 2008;Binder et al, 2008] Methylation abnormality at ICR1 in the 11p15 region hypomethylation in 37 -63% [Netchine et al, 2007;Binder et al, 2008;Bartholdi et al, 2009;Bruce et al, 2009;Abu-Amero et al, 2010;Turner et al, 2010;Vals et al, 2015b] hypermethylation 5 -10% [Gaston et al, 2001;Cooper et al, 2005Cooper et al, , 2007Sasaki et al, 2007] Methylation abnormality at ICR2 in the 11p15 region few cases with the hypomethylation of both ICRs [Begemann et al, 2011] hypomethylation in 50 -60% [Gaston et al, 2001;Cooper et al, 2005;Weksberg et al, 2010;Begemann et al, 2012b] Duplication in the 11p15 region (may involve ICR1 and/or ICR2) maternal 1 -2% [Eggermann et al, 2010a[Eggermann et al, , 2014b paternal microdeletions involving ICR1 (~5%) and microduplications of ICR2 (<1%) [Niemitz et al, 2004;Sparago et al, 2004;Bliek et al, 2009b;Demars et al, 2011;Begemann et al, 2012b;Vals et al, 2015a] Other chromosomal aberrations (including cryptic) 2% (the most frequent are 1q21 microdeletion, 12q24 microdeletion, ring chromosome 15, and deletion 15qter) [Bruce et al, 2010;Spengler et al, 2012;Fuke et al, 2013;Fokstuen and Kotzot, 2014;Azzi et al, 2015] rare cases, maternally inherited balanced translocations/inversions …”
Section: Clinical Symptoms and Diagnostic Criteria For Bwsmentioning
confidence: 99%
See 1 more Smart Citation
“…MLPA data analysis was performed with the Coffalyser software (MRC-Holland). A detailed description of the methods has been previously published [36] and is available also on the manufacturer's website (MRC-Holland, https://mlpa.com).…”
Section: Uniparental Disomy (Upd) Analysismentioning
confidence: 99%
“…SRS belongs to the group of rare diseases, its incidence is estimated to range between 1 in 3,000 to 1 in 100,000 (Price, Stanhope, Garrett, Preece, & Trembath, 1999). In the Estonian population an incidence of 1 in 70,000 has been determined (Vals et al, 2015). MRKH as a comorbidity of SRS has been reported in five cases (Abraham et al, 2015;Bellver-Pradas et al, 2001;Bliek et al, 2006;Bruce et al, 2010), among them three with ICR1 hypomethylation, and it is therefore recommended to investigate girls with SRS and primary amenorrhoea for MRKH (Wakeling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%